Do implicit measures improve suicide risk prediction? An 18‐month prospective study using different tasks. Issue 5 (1st July 2021) - Scheunemann, Jakob; Jelinek, Lena; Peth, Judith; Runde, Anne; Arlt, Sönke; Gallinat, Jürgen; Kühn, Simone
Abstract: Background: There is accumulating evidence that implicit measures improve the prediction of suicidality within a 6‐month follow‐up period in psychiatric populations. Building upon these results, we set out to expand the follow‐up period and to investigate various implicit methods. Methods: Seventy‐nine inpatients completed the Beck Scale for Suicidal Ideation (BSS) and a range of implicit measures: three implicit association tests (IATs: Death; Self‐harm–Me/Others; Self‐Harm–Good/Bad) and a subliminal priming task (with separate scores for negative and positive adjectives, each indicating the association between the primes "dying" and "growing"). After 18 months, we reached n = 52 patients and reassessed suicidal ideation, plans, and attempts. Results: In a hierarchical regression, the five implicit task indices were entered after the patient's age, gender, and BSS score at baseline. The implicit scores improved prediction of BSS scores after 18 months compared to prediction based on age, gender, and BSS score at baseline alone. However, none of the implicit measures was associated with suicide plans or attempts during the follow‐up period. Conclusion: Results suggest that implicit measures can be a useful assessment tool for the prediction of suicidal ideation, even beyond the BSS. However, long‐term prediction of suicide plans or attempts using implicit measures seems limited.